Transdermal permeability of N-Acetyl-D-Glucosamine - Capomacchia, Anthony C. (2007)
Transdermal permeation of N-acetyl-D-glucosamine (NAG), a metabolite of glucosamine was examined. Glucosamine salts are nutraceuticals used in the oral treatment of osteoarthritis. Sparse information is available regarding glucosamine and NAG transdermal or percutaneous transport and absorption. Permeability of NAG in various enhancer suspensions was evaluated by using shed snakeskin as a model membrane via Franz-type cell diffusion studies. Negligible permeability was observed for NAG in neat solutions of known membrane permeation enhancers ethanol, oleic acid, isopropyl myristate, and isopropyl palmitate, as well as from saturated solutions of NAG in water or phosphate buffer. Permeability measurements obtained from saturated solutions of NAG in DMSO and phosphate buffer solutions containing ethanol at 2%, 5%, 10%, 25%, and 50% demonstrated excellent permeation. Permeability coefficients of the phosphate buffer/ethanol solutions at 5%, 10%, and 25% were about threefold larger in value as those for saturated DMSO solution, whereas the 2% and 50% solution values were lower.